Bond flux for submerged arc welding
The bond flux for submerged arc welding, with its carefully controlled composition, addresses the challenge of achieving high tensile strength and toughness in weld metals for high Cr ferritic heat-resistant steels, even after PWHT, thereby enhancing the mechanical performance of weld metals.
Patent Information
- Application Number
- JP2021145757
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-09-07
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2041-09-07
AI Technical Summary
Existing submerged arc welding methods for high Cr ferritic heat-resistant steels fail to achieve the required mechanical performance, specifically tensile strength and toughness, even after post-weld heat treatment (PWHT).
A bond flux for submerged arc welding is developed, comprising specific mass percentages of MgO, Ca, F, Al2O3, SiO2, CO2, Na, C, and other components, which are carefully controlled to achieve optimal deoxidation, slag flowability, and arc stability, thereby enhancing the mechanical properties of the weld metal.
The proposed bond flux enables the production of weld metals with significantly improved tensile strength and toughness after PWHT, meeting the demanding mechanical performance requirements for high Cr ferritic heat-resistant steels.
Smart Images

Figure 0007658862000001 
Figure 0007658862000002 
Figure 0007658862000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a bond flux for submerged arc welding and a weld metal suitable for welding high Cr ferritic heat resistant steel. [Background technology]
[0002] Since thermal power boilers and turbines, oil refining pressure vessels, various heat-resistant and pressure-resistant steel pipes, etc. are used in high-temperature and high-pressure environments, various high-Cr ferritic heat-resistant steels are used according to the environment of use. Examples of such heat-resistant steels include A387Gr.92, which is specified in the ASTM (American Society for Testing and Materials) standard and the ASME (American Society of Mechanical Engineers) standard. Many welding materials for use with such high-Cr ferritic heat-resistant steels have already been proposed.
[0003] For example, a submerged arc welding method for 9Cr-1Mo steel is disclosed in Patent Document 1. The welding method described in Patent Document 1 is a welding method in which a wire and flux having controlled contents of contained components are combined, and it is described that cracks can be prevented and excellent high-temperature strength and toughness can be obtained. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 1-258894 Summary of the Invention [Problem to be solved by the invention]
[0005] However, in recent years, there has been a demand for further improvement in the mechanical properties of weld metal, and the required mechanical properties cannot be satisfied even when the welding method described in the above Patent Document 1 is used. Specifically, there is a demand for welding materials that can obtain weld metal with even more excellent tensile strength and toughness after PWHT (Post Weld Heat Treatment).
[0006] The present invention has been made in view of the above-mentioned circumstances, and an object of the present invention is to provide a bond flux for submerged arc welding of high Cr ferritic heat-resistant steel, which can provide a weld metal having excellent tensile strength and toughness after PWHT, and a weld metal having excellent tensile strength and toughness. [Means for solving the problem]
[0007] The above object of the present invention is achieved by the following constitution [1] relating to a bonded flux for submerged arc welding. [1] A bond flux for submerged arc welding of high Cr ferritic heat-resistant steel, For the total flux mass, MgO: 24.0% by mass or more and 35.0% by mass or less, Ca: 10.3% by mass or more and 21.9% by mass or less, F: 7.8% by mass or more and 14.0% by mass or less, Al2O3: 7.0% by mass or more and 25.0% by mass or less, SiO2: 8.0% by mass or more and 22.0% by mass or less, CO2: 1.0 mass% or more and 6.0 mass% or less, Na: 0.5% by mass or more and 4.0% by mass or less, C: Contains 0.02% by mass or more and 0.16% by mass or less, ZrO2: 4.0% by mass or less, Al: 0.80% by mass or less; A bonded flux for submerged arc welding, characterized in that the value obtained by the following formula (1) is 3.0 or more and 7.0 or less, where the MgO content in the flux is [MgO] in mass % relative to the total mass of the flux, the Ca content in the flux is [Ca] in mass % relative to the total mass of the flux, the F content in the flux is [F] in mass % relative to the total mass of the flux, the Al2O3 content in the flux is [Al2O3] in mass % relative to the total mass of the flux, the SiO2 content in the flux is [SiO2] in mass % relative to the total mass of the flux, and the CO2 content in the flux is [CO2] in mass % relative to the total mass of the flux. Formula (1): {[MgO]+1.4×([Ca]-1.055×[F])+2.055×[F]+0.5×[Al2O3]} / ([SiO2]+[CO2])
[0008] Preferred embodiments of the present invention relating to a bonded flux for submerged arc welding relate to the following [2] to [5].
[0009] [2] Furthermore, for the total flux mass, The bonded flux for submerged arc welding according to [1], characterized by containing Mn: 0.5 mass % or more and 2.5 mass % or less.
[0010] [3] Furthermore, for the total flux mass, The bonded flux for submerged arc welding according to [1] or [2], characterized by containing K: 0.5 mass% or more and 3.0 mass% or less.
[0011] [4] Furthermore, for the total flux mass, The bonded flux for submerged arc welding according to any one of [1] to [3], characterized by containing Li: 0.05 mass % or more and 0.20 mass % or less.
[0012] [5] Used with submerged arc welding wire, The wire for submerged arc welding has a mass of: C: 0.07% by mass or more and 0.12% by mass or less, Si: 0.10 mass% or more and 0.35 mass% or less, Mn: 0.40 mass% or more and 0.80 mass% or less, S: 0.001% by mass or more and 0.020% by mass or less, Ni: 0.15% by mass or more and 0.40% by mass or less, Cr: 8.0 mass% or more and 10.0 mass% or less, Mo: 0.30 mass% or more and 0.60 mass% or less, V: 0.15% by mass or more and 0.25% by mass or less, Co: 0.30 mass% or more and 0.60 mass% or less, B: 0.0003 mass% or more and 0.0030 mass% or less, Nb: 0.020 mass% or more and 0.100 mass% or less, W: 1.50% by mass or more and 2.00% by mass or less, N: 0.030% by mass or more and 0.070% by mass or less; P: 0.020% by mass or less, Cu: 0.20% by mass or less, Al: 0.020% by mass or less; The bonded flux for submerged arc welding according to any one of [1] to [4], characterized in that the balance is Fe and unavoidable impurities.
[0013] The above object of the present invention is achieved by the following configuration [6] relating to the weld metal. [6] A weld metal formed using the bond flux for submerged arc welding according to any one of [1] to [5]. Effect of the Invention
[0014] According to the present invention, it is possible to provide a bond flux for submerged arc welding of high Cr ferritic heat resistant steel, which can provide a weld metal having excellent tensile strength and toughness after PWHT, and a weld metal having excellent tensile strength and toughness. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, embodiments for carrying out the present invention will be described in detail. Note that the present invention is not limited to the embodiments described below, and can be arbitrarily modified and implemented without departing from the gist of the present invention.
[0016] The inventors of the present invention have intensively studied a submerged arc welding bond flux suitable for obtaining a weld metal that is suitable when using ASTM A387Gr.92 as a welding base material and has excellent tensile strength and toughness after PWHT. As a result, among the components in the flux, in particular, it has been found that it is effective to appropriately control the contents of MgO, Ca, F, Al2O3, SiO2, CO2, Al, and C, and to control the parameters using the contents of MgO, Ca, F, Al2O3, SiO2, and CO2.
[0017] Hereinafter, regarding the submerged arc welding bond flux according to the present embodiment, the reasons for adding components and the reasons for limiting the composition will be described in detail.
[0018] [1. Submerged Arc Welding Bond Flux] The submerged arc welding bond flux according to the present embodiment is a bond flux suitable for welding high Cr ferritic heat-resistant steel, and contains the following elements as essential elements, or may contain them as optional components.
[0019] <MgO: 24.0 mass% or more and 35.0 mass% or less> MgO is a slag-forming agent and has the effect of improving the fluidity of the slag and shaping the bead. MgO is also a component that has the effect of reducing the amount of oxygen in the weld metal and ensuring toughness. When the MgO content in the flux is less than 24.0 mass%, the effect of reducing the amount of oxygen in the weld metal is insufficient, the toughness decreases, and the bead appearance deteriorates. Therefore, the MgO content with respect to the total mass of the flux is 24.0 mass% or more, preferably 25.0 mass% or more, and more preferably 25.5 mass% or more. On the other hand, when the MgO content in the flux exceeds 35.0% by mass, slag entrainment increases and welding workability deteriorates. Therefore, the MgO content relative to the total mass of the flux is 35.0% by mass or less, preferably 34.5% by mass or less, and more preferably 34.0% by mass or less. In this embodiment, the MgO content means the value obtained by converting all the Mg contained in the flux into MgO.
[0020] <Ca: 10.3% by mass or more and 21.9% by mass or less> Ca acts as a deoxidizer and has the effect of reducing the amount of oxygen in the weld metal. When the Ca content in the flux is less than 10.3% by mass, a sufficient deoxidation effect by Ca cannot be obtained, the toughness decreases, and the bead appearance deteriorates. Therefore, the Ca content relative to the total mass of the flux is 10.3% by mass or more, preferably 11.3% by mass or more, and more preferably 11.8% by mass or more. On the other hand, when the Ca content in the flux exceeds 21.9% by mass, the slag detachability decreases. Therefore, the Ca content relative to the total mass of the flux is 21.9% by mass or less, preferably 20.9% by mass or less, and more preferably 20.4% by mass or less. Note that Ca is contained in the flux in the form of fluoride and carbonate.
[0021] <F: 7.8% by mass or more and 14.0% by mass or less> F has the effect of reducing the diffusible hydrogen amount in the weld metal and improving the low-temperature crack resistance, and also has the effect of controlling the amount of oxygen in the weld metal and shaping the bead. When the F content in the flux is less than 7.8% by mass, the amount of oxygen in the weld metal increases and the toughness decreases. Therefore, the F content relative to the total mass of the flux is 7.8% by mass or more, preferably 8.3% by mass or more, and more preferably 8.6% by mass or more. On the other hand, when the F content in the flux exceeds 14.0% by mass, the arc becomes unstable, and the bead shape and slag detachability deteriorate. Therefore, the F content based on the total mass of the flux is 14.0% by mass or less, preferably 13.7% by mass or less, and more preferably 13.4% by mass or less.
[0022] <Al2O3: 7.0% by mass or more and 25.0% by mass or less> Al2O3 is a slag-forming agent and is a component that has the effect of improving the fluidity of the slag and adjusting the bead shape. When the Al2O3 content in the flux is less than 7.0% by mass, the bead shape deteriorates. Therefore, the Al2O3 content based on the total mass of the flux is 7.0% by mass or more, preferably 7.5% by mass or more, and more preferably 8.0% by mass or more. On the other hand, when the Al2O3 content in the flux exceeds 25.0% by mass, slag entrainment increases and welding workability deteriorates. Therefore, the Al2O3 content based on the total mass of the flux is 25.0% by mass or less, preferably 24.5% by mass or less, and more preferably 24.0% by mass or less.
[0023] <SiO2: 8.0% by mass or more and 22.0% by mass or less> SiO2 is a component that has the effect of improving the fluidity of the slag and adjusting the bead shape. When the SiO2 content in the flux is less than 8.0% by mass, the bead shape deteriorates. Therefore, the SiO2 content based on the total mass of the flux is 8.0% by mass or more, preferably 8.5% by mass or more, and more preferably 9.0% by mass or more. On the other hand, when the SiO2 content in the flux exceeds 22.0% by mass, slag entrainment increases and welding workability deteriorates. Therefore, the SiO2 content based on the total mass of the flux is 22.0% by mass or less, preferably 21.0% by mass or less, and more preferably 20.5% by mass or less. In this embodiment, the content of SiO2 means the value obtained by converting all Si contained in the flux into SiO2. Also, SiO2 in the flux includes SiO2 derived from water glass used as a binder.
[0024] <CO2: 1.0 mass% or more and 6.0 mass% or less> CO2 is a component that has the effect of reducing the diffusible hydrogen content in the weld metal and improving the low-temperature cracking resistance, and also has the effect of controlling the oxygen content in the weld metal. When the CO2 content in the flux is less than 1.0 mass%, low-temperature cracking occurs. Therefore, the CO2 content based on the total mass of the flux is 1.0 mass% or more, preferably 1.1 mass% or more, and more preferably 1.2 mass% or more. On the other hand, when the CO2 content in the flux exceeds 6.0 mass%, the oxygen content in the weld metal increases and the toughness decreases. Therefore, the CO2 content based on the total mass of the flux is 6.0 mass% or less, preferably 5.5 mass% or less, and more preferably 5.0 mass% or less. Note that CO2 is contained in the flux in the form of metal carbonate. Examples of the metal carbonate include CaCO3, BaCO3, MgCO3, etc. As long as the converted value of these metal carbonates into CO2 is within the above range, the same effect can be obtained.
[0025] <Na: 0.5 mass% or more and 4.0 mass% or less> Na is a component that has the effect of improving arc stability. When the Na content in the flux is less than 0.5 mass%, the arc stability decreases and welding defects occur. Therefore, the Na content based on the total mass of the flux is 0.5 mass% or more, preferably 0.7 mass% or more, and more preferably 0.9 mass% or more. On the other hand, when the Na content in the flux exceeds 4.0% by mass, the moisture absorption of the flux increases, so the hydrogen content in the weld metal increases, and cold cracking occurs. Therefore, the Na content with respect to the total mass of the flux is 4.0% by mass or less, preferably 3.5% by mass or less, and more preferably 3.1% by mass or less.
[0026] <C: 0.02% by mass or more and 0.16% by mass or less> C is a component having the effect of improving the tensile strength. When the C content in the flux is less than 0.02% by mass, the effect of improving the tensile strength of the weld metal cannot be obtained. Therefore, the C content with respect to the total mass of the flux is 0.02% by mass or more, preferably 0.03% by mass or more, and more preferably 0.04% by mass or more. On the other hand, when the C content in the flux exceeds 0.16% by mass, the strength of the weld metal becomes too high, hot cracking is likely to occur, and the toughness decreases. Therefore, the C content with respect to the total mass of the flux is 0.16% by mass or less, preferably 0.15% by mass or less.
[0027] <ZrO2: 4.0% by mass or less (including 0% by mass)> ZrO2 is a slag-forming agent and is a component having the effect of improving the fluidity of the slag and adjusting the bead shape, but it is not necessarily contained in the flux. When ZrO2 is contained in the flux, the ZrO2 content with respect to the total mass of the flux is preferably 0.01% by mass or more, and more preferably 0.1% by mass or more. On the other hand, when the ZrO2 content in the flux exceeds 4.0% by mass, slag entrainment increases and welding workability decreases. Therefore, the ZrO2 content with respect to the total mass of the flux is 4.0% by mass or less, preferably 3.5% by mass or less, and more preferably 3.0% by mass or less. In addition, in the present embodiment, the content of ZrO2 means the value obtained by converting all Zr contained in the flux into ZrO2.
[0028] <Al: 0.80 mass% or less (including 0 mass%)> Since Al combines with N to form AlN, reducing the precipitation amount of Cr, Nb, and V carbonitrides, which are essential for ensuring creep strength, and deteriorating creep strength, it is preferable to reduce Al in the flux as much as possible. When the Al content in the flux exceeds 0.80 mass%, the bead becomes welded, and the slag detachability deteriorates. Also, since the yield of elements in the weld metal improves and the strength increases, the toughness deteriorates. Therefore, the Al content with respect to the total mass of the flux is 0.80 mass% or less, preferably 0.75 mass% or less, and more preferably 0.70 mass% or less. Note that the Al defined as 0.80 mass% or less here is contained in the flux in the form of elemental Al, Fe - Al, and Al alloys, and does not include the oxide form.
[0029] <Formula (1): 3.0 or more and 7.0 or less> The following formula (1) parameterizes the deoxidizing power of the flux components to the weld metal. When the value obtained by formula (1) increases, the deoxidizing power of the flux increases and the oxygen amount in the weld metal decreases, so the toughness can be improved. However, if it becomes too high, the slag viscosity at each temperature becomes too high, so the welding workability deteriorates. That is, by appropriately controlling the value obtained by formula (1), it is possible to achieve both an improvement in toughness and an improvement in welding workability. When the value obtained by formula (1) is less than 3.0, the deoxidizing power becomes weak and the toughness of the weld metal decreases. Therefore, the value obtained by formula (1) is 3.0 or more, preferably 3.3 or more, and more preferably 3.9 or more. On the other hand, when the value obtained by formula (1) exceeds 7.0, the shape of the weld bead deteriorates, such as the central part of the bead becoming a convex bead shape. Therefore, the value obtained by formula (1) is 7.0 or less, preferably 6.5 or less, and more preferably 6.1 or less.
[0030] Formula (1): {[MgO] + 1.4×([Ca] - 1.055×[F]) + 2.055×[F] + 0.5×[Al2O3]} / ([SiO2] + [CO2]) In the above formula (1), [MgO] is the value obtained by expressing the MgO content in the flux as a mass percentage based on the total mass of the flux, [Ca] is the value obtained by expressing the Ca content in the flux as a mass percentage based on the total mass of the flux, [F] is the value obtained by expressing the F content in the flux as a mass percentage based on the total mass of the flux, [Al2O3] is the value obtained by expressing the Al2O3 content in the flux as a mass percentage based on the total mass of the flux, [SiO2] is the value obtained by expressing the SiO2 content in the flux as a mass percentage based on the total mass of the flux, and [CO2] is the value obtained by expressing the CO2 content in the flux as a mass percentage based on the total mass of the flux.
[0031] The bonding flux for submerged arc welding according to the present embodiment preferably contains the following components in predetermined contents in addition to the above components.
[0032] <Mn: 0.5 mass% or more and 2.5 mass% or less> Mn is a component having a deoxidizing effect. When Mn is contained in the flux, if the Mn content is 0.5 mass% or more, the deoxidizing power is exerted and the weld metal becomes low in oxygen, so the toughness can be improved. Therefore, the Mn content based on the total mass of the flux is preferably 0.5 mass% or more, and more preferably 0.6 mass% or more. On the other hand, when the Mn content in the flux is 2.5 mass% or less, the balance between the strength and toughness of the weld metal can be improved. Therefore, the Mn content based on the total mass of the flux is preferably 2.5 mass% or less, more preferably 2.2 mass% or less, and even more preferably 1.9 mass% or less.
[0033] <K: 0.5 mass% or more and 3.0 mass% or less> K is an arc stabilizer and is a component contained in the flux to improve arc stability. When K is contained in the flux, if the K content is 0.5 mass% or more, the arc stability is improved, so that the welding workability can be made good. Therefore, the K content based on the total mass of the flux is preferably 0.5 mass% or more, and more preferably 0.6 mass% or more. On the other hand, when the K content in the flux is 3.0 mass% or less, the moisture absorption amount of the flux is suppressed and the hydrogen amount in the weld metal is reduced, so that the occurrence of cold cracking can be suppressed. Therefore, the K content based on the total mass of the flux is preferably 3.0 mass% or less, more preferably 2.7 mass% or less, and still more preferably 2.4 mass% or less.
[0034] <Li: 0.05 mass% or more and 0.20 mass% or less> Li is an arc stabilizer and is a component contained in the flux to improve arc stability. When Li is contained in the flux, if the Li content is 0.05 mass% or more, the arc stability is improved, so that the welding workability can be made good. Therefore, the Li content based on the total mass of the flux is preferably 0.05 mass% or more, and more preferably 0.06 mass% or more. On the other hand, when the Li content in the flux is 0.20 mass% or less, the moisture absorption amount of the flux is suppressed and the hydrogen amount in the weld metal is reduced, so that the occurrence of cold cracking can be suppressed. Therefore, the Li content based on the total mass of the flux is preferably 0.20 mass% or less, more preferably 0.18 mass% or less, and still more preferably 0.17 mass% or less.
[0035] <The balance> The submerged arc welding bond flux according to the present embodiment may contain, for example, Fe, Mo, W, Cu, etc. in addition to the above components within a range that does not interfere with the effects of the present invention. These components may exist as a single substance or as a compound.
[0036] [2. Submerged arc welding wire] The bond flux for submerged arc welding according to this embodiment is used together with a wire for submerged arc welding. Hereinafter, the reasons for adding components and the reasons for limiting the composition of the wire that is preferably used together with the bond flux for submerged arc welding according to this embodiment will be described in detail.
[0037] <C: 0.07 mass% or more and 0.12 mass% or less> C has a great influence on the hardenability and the amount of carbide precipitation in the weld metal, and functions as an austenite stabilizing element, and has an effect of suppressing the remaining of the δ-ferrite phase in the weld metal. When the C content in the wire is less than 0.07 mass%, the C content in the weld metal becomes too low, and the amount of carbide precipitation becomes insufficient. In addition, the δ-ferrite phase remains, and the desired creep strength cannot be obtained. Therefore, the C content based on the total mass of the wire is 0.07 mass% or more, preferably 0.08 mass% or more. On the other hand, when the C content in the wire exceeds 0.12 mass%, the susceptibility to hot cracking increases, and particularly, cracks are likely to occur in submerged arc welding in a narrow groove. In addition, the amount of carbide precipitation increases, significantly increasing the strength of the weld metal and deteriorating the toughness. Therefore, the C content based on the total mass of the wire is 0.12 mass% or less, preferably 0.11 mass% or less, and more preferably 0.10 mass% or less.
[0038] <Si: 0.10 mass% or more and 0.35 mass% or less> Si improves the wettability of the weld bead, functions as a deoxidizer, and has an effect of improving the strength and toughness of the weld metal. When the Si content in the wire is less than 0.10 mass%, the Si content in the weld metal becomes too low, and the weldability (for example, the wettability and fusion of the weld bead) deteriorates, and the toughness and creep strength also deteriorate. Therefore, the Si content based on the total mass of the wire is 0.10 mass% or more, preferably 0.11 mass% or more, and more preferably 0.12 mass% or more. On the one hand, when the Si content in the wire exceeds 0.35% by mass, the strength of the weld metal becomes extremely high and the toughness deteriorates. Therefore, the Si content based on the total mass of the wire is 0.35% by mass or less, preferably 0.33% by mass or less, and more preferably 0.31% by mass or less.
[0039] <Mn: 0.40% by mass or more and 0.80% by mass or less> Similar to Si, Mn is a component that functions as a deoxidizer and has the effect of improving the toughness of the weld metal. Also, Mn functions as an austenite stabilizing element and is also a component that has the effect of suppressing the remaining of the δ-ferrite phase in the weld metal. Furthermore, as will be described later, Mn also has the effect of mitigating the adverse effect of S on hot cracking susceptibility. When the Mn content in the wire is less than 0.40% by mass, the Mn content in the weld metal becomes too low, and the desired toughness cannot be obtained. Also, a soft δ-ferrite phase remains in the weld metal, and the creep strength deteriorates. Furthermore, it becomes difficult to suppress the hot cracking caused by S. Therefore, the Mn content based on the total mass of the wire is 0.40% by mass or more, preferably 0.44% by mass or more, and more preferably 0.48% by mass or more. On the other hand, when the Mn content in the wire exceeds 0.80% by mass, the Mn content in the weld metal becomes too high, the carbonitrides become unstable, and the creep strength decreases. Therefore, the Mn content based on the total mass of the wire is 0.80% by mass or less, preferably 0.78% by mass or less, and more preferably 0.77% by mass or less.
[0040] <S: 0.001% by mass or more and 0.020% by mass or less> S is a component that has the effect of lowering the surface energy of the molten pool, improving the weldability, particularly the wettability on the groove surface, and improving the bead appearance and the shape of the end stop. However, S is also a component that combines with Fe during welding to form a low-melting eutectic of Fe-FeS at the final solidification part, not only increasing the hot cracking susceptibility but also embrittling the weld metal and deteriorating the toughness. If the S content in the wire is less than 0.001% by mass, the bead shape deteriorates. Therefore, the S content with respect to the total mass of the wire shall be 0.001% by mass or more. On the other hand, if the S content in the wire exceeds 0.020% by mass, hot cracking is likely to occur and the toughness deteriorates. Therefore, the S content with respect to the total mass of the wire shall be 0.020% by mass or less, preferably 0.018% by mass or less, and more preferably 0.016% by mass or less.
[0041] <Ni: 0.15% by mass or more and 0.40% by mass or less> Ni is a component that has the effect of dissolving in the matrix of the weld metal and improving the toughness of the ferrite itself. If the Ni content in the wire is less than 0.15% by mass, the effect of improving the toughness of the ferrite cannot be obtained. Therefore, the Ni content with respect to the total mass of the wire shall be 0.15% by mass or more, preferably 0.17% by mass or more, and more preferably 0.20% by mass or more. On the other hand, if the Ni content in the wire exceeds 0.40% by mass, Ni concentrates in the final solidification part during welding, the solidification completion temperature is lowered, and the hot cracking susceptibility increases. Also, during creep deformation, the size of the carbonitrides coarsens and the creep strength decreases. Therefore, the Ni content with respect to the total mass of the wire shall be 0.40% by mass or less, preferably 0.38% by mass or less, and more preferably 0.36% by mass or less.
[0042] <Cr: 8.0% by mass or more and 10.0% by mass or less> Cr is a component that has the effect of forming carbonitrides during PWHT and improving the creep strength of the weld metal. If the Cr content in the wire is less than 8.0% by mass, the precipitation amount of the carbonitrides is insufficient and the desired creep strength cannot be obtained. Therefore, the Cr content with respect to the total mass of the wire shall be 8.0% by mass or more, preferably 8.2% by mass or more, and more preferably 8.4% by mass or more. On the one hand, when the Cr content in the wire exceeds 10.0% by mass, the solidification completion temperature decreases, the high-temperature cracking susceptibility increases, and the δ-ferrite phase remains in the weld metal, resulting in a decrease in creep strength and toughness. In addition, the slag detachability deteriorates significantly. Therefore, the Cr content based on the total mass of the wire should be 10.0% by mass or less, preferably 9.7% by mass or less, and more preferably 9.5% by mass or less.
[0043] <Mo: 0.30% by mass or more and 0.60% by mass or less> Mo is a component that has the effect of improving the creep strength of the weld metal by dissolving in Cr-based carbides or the matrix during PWHT. When the Mo content in the wire is less than 0.30% by mass, the desired creep strength cannot be obtained. Therefore, the Mo content based on the total mass of the wire should be 0.30% by mass or more, preferably 0.32% by mass or more, and more preferably 0.33% by mass or more. On the other hand, when the Mo content in the wire exceeds 0.60% by mass, the amount of solid solution in Cr-based carbides and the matrix increases excessively, the strength of the weld metal becomes extremely high, and the toughness deteriorates. Therefore, the Mo content based on the total mass of the wire should be 0.60% by mass or less, preferably 0.57% by mass or less, and more preferably 0.53% by mass or less.
[0044] <V: 0.15% by mass or more and 0.25% by mass or less> V is a component that has the effect of improving the creep strength of the weld metal by forming carbonitrides during PWHT. When the V content in the wire is less than 0.15% by mass, the desired creep strength cannot be obtained. Therefore, the V content based on the total mass of the wire should be 0.15% by mass or more, preferably 0.16% by mass or more. On the other hand, when the V content in the wire exceeds 0.25% by mass, the precipitation amount of carbonitrides increases significantly, the strength of the weld metal increases, and the toughness deteriorates. Therefore, the V content based on the total mass of the wire should be 0.25% by mass or less, preferably 0.24% by mass or less.
[0045] <Co: 0.30 mass% or more and 0.60 mass% or less> Co is a component that has the effect of improving the room temperature strength and creep strength of the weld metal. When the Co content in the wire is less than 0.30 mass%, the effect of improving the strength of the weld metal cannot be obtained. Therefore, the Co content based on the total mass of the wire is 0.30 mass% or more, preferably 0.32 mass% or more, and more preferably 0.33 mass% or more. On the other hand, when the Co content in the wire exceeds 0.60 mass%, the strength of the weld metal becomes too high and the toughness decreases. Therefore, the Co content based on the total mass of the wire is 0.60 mass% or less, preferably 0.56 mass% or less, and more preferably 0.51 mass% or less.
[0046] <B: 0.0003 mass% or more and 0.0030 mass% or less> B is a component that has the effect of stabilizing the toughness of the weld metal. When the B content in the wire is less than 0.003 mass%, the toughness of the weld metal is insufficient. Therefore, the B content based on the total mass of the wire is 0.0003 mass% or more. On the other hand, when the B content in the wire exceeds 0.0030 mass%, the strength of the weld metal becomes too high, not only causing a decrease in toughness but also increasing the susceptibility to hot cracking during welding. Therefore, the B content based on the total mass of the wire is 0.0030 mass% or less, preferably 0.0029 mass% or less, and more preferably 0.0028 mass% or less.
[0047] <Nb: 0.020 mass% or more and 0.100 mass% or less> Nb, like V, is a component that has the effect of forming carbonitrides during PWHT and improving the creep strength of the weld metal. If the Nb content in the wire is less than 0.020% by mass, the desired creep strength cannot be obtained. Therefore, the Nb content based on the total mass of the wire is 0.020% by mass or more, preferably 0.021% by mass or more, and more preferably 0.023% by mass or more. On the other hand, if the Nb content in the wire exceeds 0.100% by mass, the precipitation amount of carbonitrides significantly increases, the strength of the weld metal becomes high, and the toughness deteriorates. Also, the slag detachability significantly deteriorates. Therefore, the Nb content based on the total mass of the wire is 0.100% by mass or less, preferably 0.080% by mass or less, and more preferably 0.065% by mass or less.
[0048] <W: 1.50% by mass or more and 2.00% by mass or less> W is a component having the effect of improving the room temperature strength and creep strength of the weld metal. If the W content in the wire is less than 1.50% by mass, the effect of improving the strength of the weld metal cannot be obtained. Therefore, the Co content based on the total mass of the wire is 1.50% by mass or more, preferably 1.51% by mass or more, and more preferably 1.53% by mass or more. On the other hand, if the Co content in the wire exceeds 2.00% by mass, the strength of the weld metal becomes too high and the toughness decreases. Therefore, the Co content based on the total mass of the wire is 2.00% by mass or less, preferably 1.90% by mass or less, and more preferably 1.85% by mass or less.
[0049] <N: 0.030% by mass or more and 0.070% by mass or less> N is a component having the effect of combining with Cr, V, Nb, etc. during PWHT to form carbonitrides and improving the creep strength of the weld metal. If the N content in the wire is less than 0.030% by mass, the desired creep strength cannot be obtained. Therefore, the N content based on the total mass of the wire is 0.030% by mass or more, preferably 0.035% by mass or more, and more preferably 0.038% by mass or more. On the one hand, when the N content in the wire exceeds 0.070% by mass, the precipitation amount of carbonitrides significantly increases, the strength of the weld metal becomes high, and the toughness deteriorates. Also, the N2 gas generated during the welding process tends to remain in the molten metal, and blowholes are generated. Therefore, the N content based on the total mass of the wire should be 0.070% by mass or less, preferably 0.068% by mass or less, and more preferably 0.066% by mass or less.
[0050] <P: 0.020% by mass or less> Since P forms a low-melting compound at the final solidification part during welding, not only increases the susceptibility to hot cracking, but also embrittles the weld metal and deteriorates the toughness, it is preferable to reduce the P in the wire as much as possible. When the P content in the wire exceeds 0.020% by mass, hot cracking is likely to occur and the toughness deteriorates. Therefore, the P content based on the total mass of the wire should be 0.020% by mass or less, preferably 0.016% by mass or less, and more preferably 0.011% by mass or less.
[0051] <Cu: 0.20% by mass or less> Cu is a component that tends to cause hot cracking of the weld metal. When the Cu content in the wire exceeds 0.20% by mass, hot cracking of the weld metal is likely to occur. Therefore, the Cu content based on the total mass of the wire should be 0.20% by mass or less, preferably 0.16% by mass or less, and more preferably 0.11% by mass or less.
[0052] <Al: 0.020% by mass or less> Since Al combines with N to form AlN, reduces the precipitation amount of carbonitrides of Cr, Nb, and V essential for ensuring creep strength, and deteriorates the creep strength, it is preferable to reduce the Al in the wire as much as possible. If the Al content in the wire exceeds 0.020% by mass, the bead will seize and the slag removability will deteriorate. In addition, the yield of elements in the weld metal will improve and the strength will increase, resulting in a deterioration in toughness. Therefore, the Al content relative to the total mass of the wire is set to 0.020% by mass or less, preferably 0.016% by mass or less, and more preferably 0.012% by mass or less.
[0053] <Remainder> In the wire preferably used together with the bond flux for submerged arc welding according to the present embodiment, the balance is Fe and unavoidable impurities. Examples of the unavoidable impurities include Sn, As, Sb, Pb, Bi, etc. Among these impurities, Sn, As, and Sb are each preferably 0.005 mass% or less, and the total of Sn, As, and Sb is preferably 0.015 mass% or less, based on the total mass of the wire. Furthermore, Pb and Bi are each preferably, for example, 0.001 mass% or less with respect to the total mass of the wire. Elements other than those listed as the inevitable impurities may be contained in the wire as inevitable impurities as long as their respective contents are 0.10 mass% or less with respect to the total mass of the wire, preferably 0.08 mass% or less, and more preferably 0.06 mass% or less.
[0054] [3. Welding metal] The weld metal according to this embodiment is a weld metal formed by using the bond flux described above in [1. Bond flux for submerged arc welding]. In addition, in the weld metal according to this embodiment, various welding conditions other than the use of the bond flux for submerged arc welding according to this embodiment are not particularly limited, and normal conditions in a submerged arc welding method can be used for the type of base metal, welding voltage, welding current, welding position, etc. EXAMPLES
[0055] The present invention will be described in detail below with reference to examples and comparative examples which show the effects of the present invention.
[0056] [Submerged arc welding] First, wires with various chemical compositions and a diameter of 2.4 mm were manufactured, and bond fluxes with various chemical compositions were also manufactured. The chemical components in the wires and their contents are shown in Table 1 below, and the wire numbers used and the chemical components in the flux and their contents are shown in Table 2 below. The balance of the chemical composition of the wire shown in Table 1 below is Fe and unavoidable impurities. In addition, in the chemical composition of the bond flux shown in Table 2 below, Al is not actively added, so it is listed as "<0.80" (less than 0.80). Next, the wire and bond flux were used to perform submerged arc welding, and then post-weld heat treatment (PWHT) was performed under the following conditions. The welding conditions and PWHT conditions are shown below. The base metal used was 9Cr steel or mild steel, which was buttered with welding materials simulating the chemical composition of ASTM A387 Gr.92.
[0057] (Welding conditions) Base material thickness: 25mm Bevel angle, shape: 30°, V type Root Spacing: 13mm Polarity: DCEP: Direct Current Electrode Positive Wire diameter: 2.4mm Welding position: Downward Current: 350-450A (target: 400A) Voltage: 27-30V (target: 29V) Welding speed: 33-39cm / min (target 36cm / min) Preheating / Interpass temperature: 210~260℃ Lamination method: 8 layers, 16-17 passes
[0058] (PWHT condition) Approximately 760℃, approximately 2 hours
[0059] [evaluation] After the above-mentioned submerged arc welding, heat treatment was performed under the above-mentioned PWHT conditions, and the obtained weld metal was evaluated for room temperature strength and toughness. The specific temperature (℃) and time (hr) of the PWHT conditions, as well as the evaluation results of each test, are shown in Table 3 below.
[0060] <Room temperature strength> For the weld metal after PWHT, a tensile test was performed at room temperature in accordance with the tensile and impact test method for weld metal specified in JIS Z3111:2005 to measure the 0.2% yield stress (YS) and tensile strength (TS). The strength obtained was equivalent to that of the base metal of A387 Gr.92, and the pass criteria were set based on the tensile performance classification specified in AWS5.23. Specifically, for YS, a value of 540 MPa or more was considered to be pass, and a value of less than 540 MPa was considered to be fail. For TS, a value of 620 to 775 MPa was considered to be pass, and a value of less than 620 MPa or more than 775 MPa was considered to be fail.
[0061] <Toughness> Three test pieces were taken from the weld metal after PWHT, and a Charpy impact test was carried out at 20℃ in accordance with the Charpy impact test method for metallic materials specified in JIS Z2242. The average absorbed energy vE (J) of each test piece was then calculated to evaluate toughness. Test pieces with an average absorbed energy of 47J or more were deemed to have passed, and those with an average absorbed energy of less than 47J were deemed to have failed.
[0062] [Table 1]
[0063] [Table 2]
[0064] [Table 3]
[0065] As shown in Tables 2 and 3 above, in invention examples Nos. 1 to 7, the contents of chemical components in the bond flux for submerged arc welding are within the range of the present invention. As a result of performing submerged arc welding using these fluxes, it was possible to obtain weld metal having excellent tensile strength and toughness after PWHT.
[0066] On the other hand, in Comparative Examples Nos. 1 to 5, the values calculated by formula (1) based on the MgO, Ca, F, Al2O3, SiO2 and CO2 contents in the flux were below the lower limit of the range of the present invention, and therefore the toughness of the weld metal was reduced. In addition, in Comparative Examples Nos. 2 and 3, the tensile strength was high and exceeded the desired range. In Comparative Example No. 6, the content of ZrO2 in the flux exceeded the upper limit of the range of the present invention, and therefore the toughness of the weld metal was reduced. In Comparative Example No. 7, the MgO content exceeded the upper limit of the range of the present invention, and the F content was below the lower limit of the range of the present invention, so that the toughness of the weld metal was reduced.
Claims
1. A bond flux for submerged arc welding of high Cr ferritic heat resistant steel, comprising: For the total flux mass, MgO: 24.0% by mass or more and 35.0% by mass or less, Ca: 10.3% by mass or more and 21.9% by mass or less, F: 7.8% by mass or more and 14.0% by mass or less, A 2 O 3 :7.0 mass % or more and 25.0 mass % or less, SiO 2 :8.0 mass% or more and 22.0 mass% or less, CO 2 :1.0 mass % or more and 6.0 mass % or less, Na: 0.5% by mass or more and 4.0% by mass or less, C: 0.02% by mass or more and 0.16% by mass or less, Mn: 0.5% by mass or more and 2.5% by mass or less, K: 0.5% by mass or more and 3.0% by mass or less, Contains Li: 0.05% by mass or more and 0.20% by mass or less, ZrO 2 :4.0 mass % or less, Al: 0.80% by mass or less; The total content of the MgO, the Ca, the F, the Al 2 O 3 , the SiO 2 , the CO 2 , the Na, the C, the Mn, the K, the Li, the ZrO 2 and the Al is 94.0 mass % or more, The MgO content in the flux is represented by [MgO] in mass % relative to the total mass of the flux, the Ca content in the flux is represented by [Ca] in mass % relative to the total mass of the flux, the F content in the flux is represented by [F] in mass % relative to the total mass of the flux, and the Al content in the flux is represented by [MgO] in mass % relative to the total mass of the flux. 2 O 3 The content is expressed as mass% relative to the total mass of the flux [Al 2 O 3 ] in the flux 2 The content is expressed as mass% relative to the total mass of the flux [SiO 2 ] in the flux 2 The content is expressed as mass% relative to the total mass of the flux [CO 2 ], the value obtained by the following formula (1) is 3.0 or more and 7.0 or less. Formula (1): {[MgO] + 1.4×([Ca] - 1.055×[F]) + 2.055×[F] + 0.5×[Al 2 O 3 )} / ([SiO 2 + [CO 2 )
2. Used with submerged arc welding wire, The wire for submerged arc welding has a mass of: C: 0.07% by mass or more and 0.12% by mass or less, Si: 0.10% by mass or more and 0.35% by mass or less, Mn: 0.40% by mass or more and 0.80% by mass or less, S: 0.001% by mass or more and 0.020% by mass or less, Ni: 0.15% by mass or more and 0.40% by mass or less, Cr: 8.0% by mass or more and 10.0% by mass or less, Mo: 0.30% by mass or more and 0.60% by mass or less, V: 0.15% by mass or more and 0.25% by mass or less, Co: 0.30% by mass or more and 0.60% by mass or less, B: 0.0003% by mass or more and 0.0030% by mass or less, Nb: 0.020% by mass or more and 0.100% by mass or less, W: 1.50% by mass or more and 2.00% by mass or less, N: 0.030% by mass or more and 0.070% by mass or less; P: 0.020% by mass or less, Cu: 0.20% by mass or less, Al: 0.020% by mass or less; 2. The bonded flux for submerged arc welding according to claim 1, characterized in that the balance is Fe and unavoidable impurities.
Citation Information
Patent Citations
Ultralow hydrogen ceramic welding flux for chrome molybdenum heat resistant steel and preparation method thereof
CN103934594A
Submerged arc welding method for 9cr-1mo steel
JP1989258894A
Submerged arc welding method for high-cr ferritic heat resisting steel
JP1994039587A
Welding wire for high crome ferrite wire
JP1997267190A
SINGLE SUBMERGED ARC WELDING METHOD OF HIGH Cr GROUP CSEF STEEL
JP2016022500A